Mechanisms and benefits of cardiac rehabilitation in individuals with stroke: emerging role of its impact on improving cardiovascular and neurovascular health - Cuccurullo, Sara J.; Fleming, Talya K.; Petrosyan, Hayk; Hanley, Daniel F.; Raghavan, Preeti (Frontiers in Cardiovascular Medicine, 2024)
Human and animal studies have demonstrated the mechanisms and benefits of aerobic exercise for both cardiovascular and neurovascular health. Aerobic exercise induces neuroplasticity and neurophysiologic reorganization of brain networks, improves cerebral blood flow, and increases whole-body VO2peak (peak oxygen consumption). The effectiveness of a structured cardiac rehabilitation (CR) program is well established and a vital part of the continuum of care for people with cardiovascular disease. Individuals post stroke exhibit decreased cardiovascular capacity which impacts their neurologic recovery and extends disability. Stroke survivors share the same risk factors as patients with cardiac disease and can therefore benefit significantly from a comprehensive CR program in addition to neurorehabilitation to address their cardiovascular health. The inclusion of individuals post-stroke into a CR program, with appropriate adaptations, can significantly improve their cardiovascular health, promote functional recovery, and reduce future cardiovascular and cerebrovascular events thereby reducing the economic burden of stroke.